Growing vegetables and flowering plants in a greenhouse supplied with swine-building exhaust air - J K Greig; C K Spillman; B A Koch (Kansas Agricultural Experiment Station Research Reports, 1982)
Exhaust air from a Kansas State University swine-farrowing house provides CO2 and possibly other gases that are being used by vegetable plants in a KSU greenhouse. In addition, a rock-storage system reduces fuel requirements of the greenhouse. Tomatoes and cucumbers have been the major food crops studied, but transplant production of geraniums, marigolds, snapdragons, and calendula also has been studied. Poinsettias were grown as a fall crop in 1980 and again in 1982.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Exhaust air; Vegetables; Flowering plants